INTERACTIVE INTERACTION AS ONE OF THE CONDITIONS OF EFFECTIVE ORGANIZATION OF THE TEACHING PROCESS IN HIGHER EDUCATION INSTITUTIONS (Pedagogy of Higher and Secondary Education, 2022)
In the article the author makes the attempt to substantiste the essence of interaction, its kinds and mechanisms.
Keywords: interaction; kinds of interaction; parties of interaction; mutual education; co-education